The impact of bariatric surgery on urinary incontinence: a systematic review and meta‐analysis. (11th July 2019) - Lee, Yung; Yu, James; Tikkinen, Kari A.O.; Pędziwiatr, Michał; Major, Piotr; Aditya, Ishan; Krakowsky, Yonah; Doumouras, Aristithes G.; Gmora, Scott; Anvari, Mehran; Hong, Dennis
Abstract : Objectives: To systematically review and meta‐analyse the impact of bariatric surgery on obese patients with urinary incontinence (UI). Methods: A search of the Medical Literature Analysis and Retrieval System Online (MEDLINE), the Excerpta Medica dataBASE (EMBASE), Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL), and PubMed to June 2018 was performed using methods pre‐published on the International Prospective Register of Systematic Reviews (PROSPERO). Reporting followed the Preferred Reporting Items for Systematic Review and Meta‐analysis (PRISMA) guidelines. Studies comparing UI status in obese patients before and after bariatric surgery were included. Primary outcomes were the improvement or complete resolution of any UI, stress UI (SUI), and urgency UI (UUI). Secondary outcomes were validated UI questionnaire scores. The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach assessed overall quality of evidence. Results: In all, 33 cohort studies (2910 patients) were included (median follow‐up 12 months). Bariatric surgery resulted in improvement or resolution of any UI in 56% (95% confidence interval [CI] 48–63%), SUI in 47% (95% CI 34–60%), and UUI in 53% (95% CI 32–73%) of patients. Moreover, bariatric surgery significantly decreased ( P <  0.001) questionnaire scores such as: the Urogenital Distress Inventory by 13.4 points (95% CI 7.2–19.6), International Consultation on Incontinence Questionnaire by 4.0 points (95% CI 2.3–5.7), and Incontinence Impact Questionnaire by 5.3 points (95% CI 3.9–6.6). However, worsening or new onset of UI was present in 3% of patients. The quality of evidence was very low for all outcomes. Conclusion: Half of obese patients report improvement or resolution of UI after bariatric surgery, but overall the quality of evidence is very low. Comparative studies examining the benefits of bariatric surgery in obese patients with UI are warranted.